Thionated perylene diimides with intense absorbance in the near-IR. Issue 10 (22nd December 2015) - Llewellyn, Ben A.; Davies, E. Stephen; Pfeiffer, Constance R.; Cooper, Mick; Lewis, William; Champness, Neil R.
Abstract : Combining thionation and amine substitution of perylene diimides leads to intense absorption maxima in the NIR and, upon reduction, strong absorption in the SWIR. Abstract : A synthetic strategy involving a combination of tetra-thionation and amine substitution in the bay region of a perylene diimide (PDI) leads to remarkable examples of neutral PDIs with intense absorption maxima in the near infrared. Generation of the corresponding monoanions red shifts the absorption profile to give short-wavelength infrared bands.